The Analysis of Factors Affecting Multi-dimensional Poverty of the Khmer Ethnic in Tra Vinh Province, Vietnam - Nguyen, Ha Hong (International Journal of Economics and Financial Issues, 2018)
The analysis of factors affecting multi-dimensional poverty of the Khmer ethnic minority in Tra Vinh province was conducted by the use of primary data collection, direct interviews with 300 Khmer ethnic households living in 07 districts and cities in Tra Vinh province. The research has found the factors that affect multi-dimensional poverty of the Khmer households: the occupation of household owners, the educational level, and dependency ratio, the participation in health insurance and telecommunications services. In particular, the occupation, educational level and dependency ratio are the factors that have the most impact on the poor status of the Khmer ethnic people in Tra Vinh province. Since then, the research has proposed a number of solutions such as vocational training to raise incomes, building preferential credit policies, building telecommunication infrastructure and medical services, etc. so as to raise incomes, life stabilization, multi-dimensional poverty reduction for the Khmer ethnic people in Tra Vinh province in the future. Keywords: Income, occupation, Khmer, education, health insurance JEL Classifications: I13, I2, I3